2003
DOI: 10.1002/ijc.11523
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of BRAF are associated with extensive hMLH1 promoter methylation in sporadic colorectal carcinomas

Abstract: In the development of colorectal cancer (CRC), it is now widely accepted that some forms of genetic instability lead to the sequential accumulation of genetic alterations and consequently develop carcinomas. 1 RAS activation in the MAP kinase cascade is supposed to constitute a part of the primary events in colorectal carcinogenesis, and the KRAS gene mutations have been found in about 30 -40% cases of sporadic CRCs. [2][3][4] Recently, activating BRAF mutations have been found almost invariably in melanoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 30 publications
7
93
0
1
Order By: Relevance
“…BRAF, which encodes a RAF family member that functions downstream of RAS, has been reported to be somatically mutated in a number of human cancers. 3,5,25 Recently, activating mutations of BRAF have been frequently observed in microsatellite unstable (MSI+) colorectal carcinomas, in which mutations of BRAF and K-ras have been reported to be mutually exclusive. 5 Another recent study has suggested that alterations of the RAS pathway, both by RAS and BRAF mutations, contribute to the pathogenesis of stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…BRAF, which encodes a RAF family member that functions downstream of RAS, has been reported to be somatically mutated in a number of human cancers. 3,5,25 Recently, activating mutations of BRAF have been frequently observed in microsatellite unstable (MSI+) colorectal carcinomas, in which mutations of BRAF and K-ras have been reported to be mutually exclusive. 5 Another recent study has suggested that alterations of the RAS pathway, both by RAS and BRAF mutations, contribute to the pathogenesis of stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,25 Recently, activating mutations of BRAF have been frequently observed in microsatellite unstable (MSI+) colorectal carcinomas, in which mutations of BRAF and K-ras have been reported to be mutually exclusive. 5 Another recent study has suggested that alterations of the RAS pathway, both by RAS and BRAF mutations, contribute to the pathogenesis of stomach cancer. 25 Also, mutations in BRAF and K-ras have been found to characterise the development of lowgrade ovarian serous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations